Late-onset endometrial ablation failure - Morris Wortman (Elsevier, 2017)
Endometrial ablation, first reported in the 19th century, has gained wide acceptance in the gynecologic community as an important tool for the management of abnormal uterine bleeding when medical management has been unsuccessful or contraindicated. The introduction of global endometrial ablation (GEA) devices beginning in 1997 has provided unsurpassed safety addressing many of the concerns associated with their resectoscopic predecessors. As of this writing the GEA market has surpassed a half-million devices in the United States per annum and has an expected compound annual growth rate (CAGR) projected to be 5.5% from 2016 to 2024. While the short term safety and efficacy of these devices has been reported in numerous clinical trials we only recently are becoming aware of the high incidence of late-onset endometrial ablation failures (LOEAFs) associated with these procedures. Currently, about a quarter of women who undergo a GEA procedure will eventually require a hysterectomy while an unknown number have less than satisfactory results. In order to reduce these suboptimal outcomes physicians must better understand the etiology and risk factors that predispose a patient toward the development of LOEAF as well as current knowledge of patient and procedure selection for EA as well as treatment options for these delayed complications.